Relationship between a Child's Cognitive Skills Andthe Inclusion of Age Appropriate Toys in the Home Environment - Somayeh Kavousipor; Fariba Golipour; Mahshid Hekmatnia (Shiraz University of Medical Sciences, 2016)
Background: With respect to the significance of toys, playing, and the home environment on children's development, the present study investigates the relationship between gross motor and fine motor toys existing athome and in the home environment, withchild cognitive skills such as problem-solving, communication, and personal-social skills. Methods: This cross-sectional study was conducted with the participation of 140 mother-child couples (children between the ages of 18 and42 months of age) randomly selected from the healthcare centers of the city of Shiraz. Employing the questionnaire of the Affordance in the Home Environment for Motor Development-Self Report (AHEMD-SR) and the Ages & Stages Questionnaires®, Third Edition (ASQ-3™), both of which have validity and reliability in Iran, the required data were collected,the relationship between children's cognitive development was evaluated by ASQ, and the toys and the home environment evaluated by AHEMD-SR was calculated by the Pearson correlation coefficient. Results: Studying the relationships revealed that playing with toys related to gross movement stimulation have weak correlations with all three skills of theASQ considered in the present study, i.e.,communication(r=0.218, P=0.001), problem solving(r=0.168, P=0.02), andpersonal-social skills(r=0.187, P=0.04). Nevertheless, toys related to fine movement stimulation had very low correlations.In addition, the final score of the AHEMD-SR, including toys and other aspects of the home environment, indicate an important relationship with the personal-social skill item of the ASQ (r=0.367, P=0.02). Conclusion: With regard to the findings of the present study, theinside-home space characteristic and playing with appropriate toys maymotivate the child's cognitive development. Making parents and healthcare officials aware ofthe appropriate toys and the home environment, therefore, seems to be necessary.